Head first Android development : a brain-friendly guide - Griffiths, Dawn; Griffiths, David, 1969- (Head first series., 2017)
Presents an introduction to Android development, with information on building interactive apps, creating the user interface, setting up databases, using action bars, and making apps fit in with Material Design.